1984
DOI: 10.1190/1.1441706
|View full text |Cite
|
Sign up to set email alerts
|

Toward a three‐dimensional automatic interpretation of potential field data via generalized Hilbert transforms: Fundamental relations

Abstract: The paper extends to three dimensions (3-D) the two‐dimensional (2-D) Hilbert transform relations between potential field components. For the 3-D case, it is shown that the Hilbert transform is composed of two parts, with one part acting on the X component and one part on the Y component. As for the previously developed 2-D case, it is shown that in 3-D the vertical and horizontal derivatives are the Hilbert transforms of each other. The 2-D Cauchy‐Riemann relations between a potential function and its Hilbert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
271
0
20

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 527 publications
(292 citation statements)
references
References 0 publications
1
271
0
20
Order By: Relevance
“…More recently the method has been expanded to 3D problems, [15], [16], as a mapping and depth-to-source technique and as a way to learn about the nature of the causative magnetization.…”
Section: Analytic Signal Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently the method has been expanded to 3D problems, [15], [16], as a mapping and depth-to-source technique and as a way to learn about the nature of the causative magnetization.…”
Section: Analytic Signal Methodsmentioning
confidence: 99%
“…The target for specific surveys are often small-scale structures buried at shallow depths, and the magnetic responses of these targets are embedded in a regional field that arises from magnetic sources that are usually larger or deeper than the targets or are located farther away. Correct estimation and removal of the regional field from the initial field observations yields the residual field produced by the target sources [15]. The extracted residual anomalies are often useful for structural mapping or qualitative interpretation based on visual inspection of the data.…”
Section: The Residual Mapmentioning
confidence: 99%
“…He (Nabighian, 1984) generalized the 2D analytic signal to 3D and showed that the Hilbert transform of any potential field satisfies the Cauchy-Riemann relations. Roest et al, (1992) extended the definition of the analytic signal of the potential field Hsu et al, (1998) showed that vertical derivatives of the analytic signal amplitude can be used to estimate depth to the top surface of the dike like and step like structures.…”
Section: Analytic Signal Techniquesmentioning
confidence: 99%
“…O sinal analítico tridimensional corresponde a uma gama de métodos automáticos que são baseados no uso dos gradientes vertical e horizontais das anomalias (Nabighian, 1984;Roest et al, 1992). Tem como característica amplificar os curtos e atenuar os longos comprimentos de onda do sinal geofísico nas três direções ortogonais, realçando as bordas e os contatos de feições geológicas e falhas.…”
Section: Magnetometriaunclassified